Trends in sociodemographic and lifestyle factors associated with sedentary behavior among Brazilian adults - Trindade,Lucas Akio Iza (2021)
ABSTRACT: Objective: To analyze sociodemographic and lifestyle factors associated with screen-based sedentary behavior (watching television ≥ 3 hours/day) among adult individuals in Brazil. Methods: Quantitative analysis of ten editions of the cross-sectional health survey VIGITEL, representative at the population level. Individuals from states’ capitals living in households with land-line telephone were randomly selected and interviewed with a structured questionnaire, through the telephone. A multivariate logistic regression model was estimated for identification of factors associated with screen-based sedentary behavior. Results: There was stability in trends referring to prevalence of sedentary behavior from 2008 to 2017. Prevalence of sedentary behavior was higher between individuals with unhealthier lifestyles: consumption of < two in natura food items (vegetables, fruits, and beans) per day (26.73% [95%CI 25.2 – 28.31]) in comparison with ≥ two items per day (23.79% [95%CI 21.92 – 25.77]); consumption of soft drinks ≥ five days per week (31.24% [95%CI 29.58 – 32.95]) than < five days per week (23.82% [95%CI 22.2 – 25.52]); and practice of < 150 minutes of physical activity per week (28.2% [95%CI 26.17 – 30.33]) than ≥ 150 minutes per week (22.54% [95%CI 21.27 – 23.86]). Regular consumption of in natura food items (OR = 0.984), practice of physical activity (OR = 0.798), and living in richer municipality (OR = 0.826) represented protective factors in relation to screen-based sedentary behavior, whilst regular consumption of soft drinks (OR = 1.440), smoking (OR = 1.375) and alcohol abuse (OR = 1.334) represented risk factors. Conclusion: The adoption of screen-based sedentary behavior among adult individuals in Brazil presented significant association with modifiable behavioral factors in the period 2008–2017.